2015
DOI: 10.2147/ott.s91511
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin decreases invasiveness, deactivates STAT3 signaling, and reverses interleukin-6 induced epithelial–mesenchymal transition and matrix metalloproteinase secretion of pancreatic cancer cells

Abstract: Luteolin, a flavone, has been shown to exhibit anticancer properties. Here, we investigated whether luteolin affects epithelial–mesenchymal transition (EMT) and invasiveness of pancreatic cancer cell lines and their underlying mechanism. Pancreatic cancer cell lines PANC-1 and SW1990 were used in our study, and their EMT characters, matrix metalloproteinase (MMP) expression level, invasiveness, and signal transducer and activator of transcription 3 (STAT3) activity were determined after luteolin treatment. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 46 publications
4
52
0
Order By: Relevance
“…Signal transducer and activator of transcription 3 is activated by numerous cytokine receptor‐associated tyrosine kinases, growth factor receptors with intrinsic tyrosine kinase activity, and oncogenic proteins; making STAT3 signaling central to the regulation of cancer invasion and metastasis. Moreover, our previous study showed that several genes downstream of the activated STAT3 pathway were closely related to EMT . In the present study, DMKN‐shRNA‐transfected PDAC cells showed lower expression of N‐cadherin, vimentin, and Snail, but higher expression of E‐cadherin.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Signal transducer and activator of transcription 3 is activated by numerous cytokine receptor‐associated tyrosine kinases, growth factor receptors with intrinsic tyrosine kinase activity, and oncogenic proteins; making STAT3 signaling central to the regulation of cancer invasion and metastasis. Moreover, our previous study showed that several genes downstream of the activated STAT3 pathway were closely related to EMT . In the present study, DMKN‐shRNA‐transfected PDAC cells showed lower expression of N‐cadherin, vimentin, and Snail, but higher expression of E‐cadherin.…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, our previous study showed that several genes downstream of the activated STAT3 pathway were closely related to EMT. (31) In the present study, DMKN-shRNA-transfected PDAC cells showed lower expression of N-cadherin, vimentin, and Snail, but higher expression of E-cadherin. At the same time, STAT3 activity also modulated the level of DMKN.…”
Section: Discussionsupporting
confidence: 52%
“…Bioassay-directed fractionation techniques led to the isolation of isoorientin as the main hypoglycemic component in Gentiana olivieri 8. Our team confirmed that luteolin has a strong anticancer effect in PC 9. The effects of isoorientin, as a 6-C-glucoside of luteolin, on cancer need to be identified.…”
Section: Introductionmentioning
confidence: 68%
“…Plants rich in luteolin have been used in Chinese traditional medicine to treat various diseases, such as hypertension, inflammatory disorders, and cancer [3, 4]. The anti-cancer activities of luteolin have been demonstrated in many cancer cells, such as pancreatic cancer, prostate cancer, breast cancer, colorectal cancer, and ovarian cancer [5-8]. In addition, luteolin could upregulate the mRNA expression level of intercellular adhesion molecule-1, a tumor suppressor gene [9], in mouse H22 hepatoma cells [10].…”
Section: Introductionmentioning
confidence: 99%